Optical fiber sensing based on reflection laser spectroscopy - Gagliardi, Gianluca; Salza, Mario; Ferraro, Pietro; Chehura, Edmon; Tatam, Ralph P.; Gangopadhyay, Tarun K.; Ballard, Nicholas; Paz-Soldan, Daniel; Barnes, Jack A.; Loock, Hans-Peter; Lam, Timothy T-Y; Chow, Jong H.; et al. (MDPI, 2010)
An overview on high-resolution and fast interrogation of optical-fiber sensors relying on laser reflection spectroscopy is given. Fiber Bragg-gratings (FBGs) and FBG resonators built in fibers of different types are used for strain, temperature and acceleration measurements using heterodyne-detection and optical frequency-locking techniques. Silica fiber-ring cavities are used for chemical sensing based on evanescent-wave spectroscopy. Various arrangements for signal recovery and noise reduction, as an extension of most typical spectroscopic techniques, are illustrated and results on detection performances are presented.
Keywords: Fiber Bragg gratings; fiber resonator; Pound-Drever-Hall method; frequency locking; laser-frequency modulation; high-birefringence fiber